2018
DOI: 10.1016/j.myc.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes of trehalose content and trehalose-degrading activity during fruit-body formation and autolysis in Pleurotus sp.

Abstract: We studied how the content and degrading activity of trehalose changed during fruit-body development and autolysis. During the process of autolysis, the trehalose content of whole fruit-bodies decreased sharply whereas the trehalose-degrading activity increased toward the inner region (regions 5 and 4) from the outer region (region 6) of the pilei (during stage 5-9 of autolysis). Conversely, the trehalose content during autolysis decreased toward the inner region (regions 5 and 4) from the outer region (region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The optimal temperature for recombinant trehalase was 40 ºC ( Fig. 5C ), which was similar to those observed for T. matsutake (40 ºC), L. edodes (40 ºC), S. cerevisiae (40-45 ºC), and Bombyx mori (40-45 ºC) ( Kusuda et al, 2010 ; Arastoo et al, 2018 ; Biswas & Ghosh, 1996 ; Huang, Furusawa, Sadakane, & Sugimura, 2006 ). In contrast, the optimal temperature (60 ºC) for the trehalase from Humicola grisea was higher than that of Pleurotus sp.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The optimal temperature for recombinant trehalase was 40 ºC ( Fig. 5C ), which was similar to those observed for T. matsutake (40 ºC), L. edodes (40 ºC), S. cerevisiae (40-45 ºC), and Bombyx mori (40-45 ºC) ( Kusuda et al, 2010 ; Arastoo et al, 2018 ; Biswas & Ghosh, 1996 ; Huang, Furusawa, Sadakane, & Sugimura, 2006 ). In contrast, the optimal temperature (60 ºC) for the trehalase from Humicola grisea was higher than that of Pleurotus sp.…”
Section: Resultssupporting
confidence: 76%
“…Fungi and yeast trehalases also exhibit optimal activity around pH 5.0 ( Biswas & Ghosh, 1996 ; Bharadwaj & Maheshwari, 1999 ). Arastoo et al (2018) reported that the pH in the fruit body is weakly acidic during fruit-body development ( Arastoo et al, 2018 ). It is expected that acid trehalase exists in a stable state in fruit bodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The texture change was due to the destruction of the cell structure and membrane components, which activated autolytic enzymes and aggravated softening. 33 Aroma Profiles. A total of 50 VOCs were identified in L. edodes (Table 1) and were mainly classified into eight groups: alcohols (10), aldehydes (7), esters (13), ketones (6), alkenes (6), acids (4), alkanes (2), and others (2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…edodes. The texture change was due to the destruction of the cell structure and membrane components, which activated autolytic enzymes and aggravated softening …”
Section: Resultsmentioning
confidence: 99%